2005
DOI: 10.1529/biophysj.104.048132
|View full text |Cite
|
Sign up to set email alerts
|

Domain Formation Induced by the Adsorption of Charged Proteins on Mixed Lipid Membranes

Abstract: Peripheral proteins can trigger the formation of domains in mixed fluid-like lipid membranes. We analyze the mechanism underlying this process for proteins that bind electrostatically onto a flat two-component membrane, composed of charged and neutral lipid species. Of particular interest are membranes in which the hydrocarbon lipid tails tend to segregate owing to nonideal chain mixing, but the (protein-free) lipid membrane is nevertheless stable due to the electrostatic repulsion between the charged lipid he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
97
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(103 citation statements)
references
References 26 publications
6
97
0
Order By: Relevance
“…39 Khelashvili et al employed a dynamic Monte Carlo simulation to explore the protein diffusion on mixed membrane and corresponding charged lipid reorganization. 10 Various coarse-grained models, which consider the lipids within regular solution theory and the macromolecule as a homogeneous flat surface, 40 a finite cylinder, 41,42 hard spheres, 43 rectangles, 44 or as a flexible polyelectrolyte, 8,45 have been developed. These models provided straightforward descriptions to the macromolecule/PIP 2 interaction, and showed that the extent of lipid segregation, the lipid dynamic heterogeneity behaviors, and the corresponding entropy and free energy variations are critically dependant on the shape, charge, and concentration of the adsorbing macromolecules.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 Khelashvili et al employed a dynamic Monte Carlo simulation to explore the protein diffusion on mixed membrane and corresponding charged lipid reorganization. 10 Various coarse-grained models, which consider the lipids within regular solution theory and the macromolecule as a homogeneous flat surface, 40 a finite cylinder, 41,42 hard spheres, 43 rectangles, 44 or as a flexible polyelectrolyte, 8,45 have been developed. These models provided straightforward descriptions to the macromolecule/PIP 2 interaction, and showed that the extent of lipid segregation, the lipid dynamic heterogeneity behaviors, and the corresponding entropy and free energy variations are critically dependant on the shape, charge, and concentration of the adsorbing macromolecules.…”
Section: Introductionmentioning
confidence: 99%
“…10,20,21,35 Studies supported the conclusion that the variation of the net charge of macromolecules and salt solution ionic concentration may drastically affect the segregation of charged lipids 5,37 and mediate macromolecules adsorption on the membrane. 42 Thus, systematic investigations of the influence of the cooperativity effect and electrostatic interaction of the macromolecules, and solution screening effect on the static and kinetic properties of PIP 2 , as well as the relative macromolecule dynamics can help not only the understanding of the biophysical processes, but also the development of disease therapy by controlling the segregation and mobility of PIP 2 . 1 In the previous study, we employed Monte Carlo simulation to investigate the influence of solution ionic strength on adsorption/desorption behaviors and the corresponding conformational variations of the polyelectrolyte on mixed lipid membranes.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism by which charged peripheral membrane proteins can induce domain formation has recently been proposed (Mbamala et al, 2005). Recently, it was demonstrated that NAP-22 peptide inserts into membranes, sequesters PtdIns(4,5)P 2 in a cholesteroldependent manner, and induces formation of a cholesterol-depleted domain (Epand et al, 2004(Epand et al, , 2005a.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the number of theoretical and computational studies on the interaction of proteins [72][73][74][75][76] and polyelectrolytes [77][78][79] with fluid lipid membranes has increased in recent years. It was observed that the adsorption of macromolecules induces the demixing of the lipids in the membrane and that the demixing, in turn, increases the binding energy of the macromolecule to the membrane.…”
Section: Polyelectrolyte Condensation At Responsive Surfacesmentioning
confidence: 99%